A selective electrochemical sensor for caffeic acid and photocatalyst for metronidazole drug pollutant - A dual role by rod-like SrV2O6 - R. Karthik (Nature Portfolio, 2017)
Abstract In the present study, well-defined one-dimensional (1D) rod-like strontium vanadate (SrV2O6) was prepared by simple hydrothermal method without using any other surfactants/templates. The successful formation of rod-like SrV2O6 was confirmed by various analytical and spectroscopic techniques. Interestingly, for the first time the dual role of as-prepared rod-like SrV2O6 were employed as an electrochemical sensor for the detection of caffeic acid (CA) as well as visible light active photocatalyst for the degradation of metronidazole (MNZ) antibiotic drug. As an electrochemical sensor, the SrV2O6 modified glassy carbon electrode (GCE) demonstrated a superior electrocatalytic activity for the detection of CA by chronoamperometry and cyclic voltammetry (CVs). In addition, the electrochemical sensor exhibited a good current response for CA with excellent selectivity, wide linear response range, lower detection limit and sensitivity of 0.01–207 µM, 4 nM and 2.064 μA μM−1cm−2, respectively. On the other hand, as-synthesized rod-like SrV2O6 showed highly efficient and versatile photocatalytic performances for the degradation of MNZ, which degrades above 98% of MNZ solution under visible light irradiation within 60 min. The obtained results evidenced that the improvement of rod-like SrV2O6 might be a resourceful electrocatalyst and photocatalyst material in the probable applications of environmental and biomedical applications.